Sign Language Acquisition - and Brentari, Diane (Sign Language Phonology, 2019)
Phonological acquisition and the milestones associated with it have been an important testing ground for theoretical claims since the inception of generative phonology, and the theme of this chapter builds on those from previous chapters. We have described how a sign language phonological system is influenced by the visual modality and by iconicity, how it is processed and how it emerges. We now add data from sign language acquisition to this picture, asking what evidence there is for the units proposed so far in the phonological system of a child or infant.Typical first-language (L1) phonological acquisition is a critical piece in any child’s development as she makes contact with the world, and as we will see, it is also an important stepping-stone for reading. We also address acquisition in several other circumstances where sign language is acquired, as it pertains to second-language (L2) learners, late learners of an L1, and bilingual development. These populations are unique in ways that will become clear as they are introduced throughout the chapter.
Keywords: Björn-2026-02-22; first language acquisition; late first language acquisition; movement migration; phonology- literacy; second language acquisition